2023
DOI: 10.26502/fccm.92920314
|View full text |Cite
|
Sign up to set email alerts
|

False Atrial Fibrillation Alerts from Smartwatches are Associated with Decreased Perceived Physical Well-being and Confidence in Chronic Symptoms Management

Abstract: Wrist-based wearables have been FDA approved for AF detection. However, the health behavior impact of false AF alerts from wearables on older patients at high risk for AF are not known. In this work, we analyzed data from the Pulsewatch (NCT03761394) study, which randomized patients (≥ 50 years) with history of stroke or transient ischemic attack to wear a patch monitor and a smartwatch linked to a smartphone running the Pulsewatch application vs to only the cardiac patch monitor over 14 days. At baseline and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, although false alerts have been shown to reduce perceived physical well-being, the fi nancial impact of false-positive detections is not well understood. 32 As with all medical tests, the positive predictive value varies signifi cantly based on the patient population. An important tenet of Bayesian reasoning is that the posttest probability depends on the pretest probability.…”
Section: False-positive Results and Pretest Probabilitymentioning
confidence: 99%
“…However, although false alerts have been shown to reduce perceived physical well-being, the fi nancial impact of false-positive detections is not well understood. 32 As with all medical tests, the positive predictive value varies signifi cantly based on the patient population. An important tenet of Bayesian reasoning is that the posttest probability depends on the pretest probability.…”
Section: False-positive Results and Pretest Probabilitymentioning
confidence: 99%
“…Among DL methods, CNNs were the most commonly used. Tran et al (2023) developed a CNN to analyze ECG data, exploring the impact of false ECG alerts on patient-reported health outcomes. Giskes et al (2023) deployed AF selfscreening stations in clinical waiting areas incorporating software to screen patient records and ECGs, identifying those potentially benefiting from treatment.…”
Section: Atrial Fibrillation Risk Stratification With Deep Learningmentioning
confidence: 99%
“…This decrease in accuracy is likely due to the increased challenge of these multi-factorial tasks. While ECG signals remain extensively studied due to their diagnostic richness (D. Han et al, 2022b;Tran et al, 2023), promising works have also leveraged diverse, complementary data sources. D. Han et al (2022b) employed a hybrid ML learning approach for assessing AF risk in ischemic stroke patients while Tran et al (2023) developed an innovative DL method for detecting false AF alerts.…”
Section: Most Influential Studies For Af Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol may also be informative for the scalability of other technology-based interventions involving large amounts of data. For example, recent studies exploring the impact of wearable technology on the identification and treatment of atrial fibrillation have identified the importance of filtering out excess data to maximize the proportion of cases requiring intervention that are escalated to the clinical team [56][57][58][59][60][61][62]. We have considered these factors here to ensure that the Scene Health team is empowered to engage with participants and assess…”
Section: Adhere Emphasizes Collaboration To Maximize Safety While Pro...mentioning
confidence: 99%